1998
DOI: 10.1063/1.367151
|View full text |Cite
|
Sign up to set email alerts
|

Vertical metrology using scanning-probe microscopes: Imaging distortions and measurement repeatability

Abstract: We report a study of the repeatability as limited by instrumental imaging distortions in scanning-probe microscope (SPM) measurements of the heights of nominal 44 and 88 nm steps in calibration artifacts. By imaging the same series of locations on different days, we are able to distinguish sample variations from variations originating in the imaging process. In particular, the value and repeatability of the measured step heights are found to depend upon the algorithm used to infer the step height from the SPM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Edwards et al [9] reported that tip wear could contribute a significant systematic error in step height measurement. When a measured sample surface includes sharp features with radius smaller than the tip radius, the scanned image consists of a combination of the tip shape and the surface, referred to as tip artifacts [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Edwards et al [9] reported that tip wear could contribute a significant systematic error in step height measurement. When a measured sample surface includes sharp features with radius smaller than the tip radius, the scanned image consists of a combination of the tip shape and the surface, referred to as tip artifacts [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lateral resolution of an AFM can be worsened due to tip wear and increase in contact diameter between the tip and the surface [6]. Also, artifacts are generated in the topography image due to degradation of the tip by the convolution effect [6,7]. In addition, the realization of SPM-based applications has been often limited due to the reliability problem induced by the tip damage.…”
Section: Introductionmentioning
confidence: 99%
“…1 This tip degradation introduces artifacts in imaging, which leads to errors in step height measurements. 1,2 The wear of tip material during scanning also affects nanopatterning techniques, such as dip pen nanolithography, 3,4 nanofountain probe patterning, [5][6][7][8][9] and scanning probe contact printing, 10,11 as the size of patterned features depends on the radius of the tip. Knowing the extent of tip wear is also important for hardness measurements using AFM nanoindentation or atomic force acoustic microscopy, 12,13 as the interpretation of results depends on the tip radius.…”
Section: Introductionmentioning
confidence: 99%